Injuries to the Chest Wall Diagnosis and Management - McKee, Michael D.; Schemitsch, Emil H. (Springer International Publishing : Imprint: Springer, 2015)
Up-to-date and multidisciplinary, this text brings together all of the latest research and clinical treatment strategies for the management of injuries to the chest wall and rib cage. The management of trauma to the chest wall, especially "flail chest" injuries, has been relatively stagnant for many years. Non-operative treatment has been the standard of care, and despite some advances, has reached the point where there is little new to offer a severely traumatized patient. However, recently, there has been a dramatic increase in the interest in surgical fixation of unstable chest wall injuries. Specifically, plate or intramedullary nail fixation of multiple rib fractures has rapidly become the state-of-the-art in many trauma centers, and there have multiple research papers, reviews, new fixation devices, and instructional courses at national level meetings on this topic. This book assembles a diverse group of experts in the field-orthopedic surgeons, trauma surgeons, anesthetists, basic science researchers-to produce the definitive work on this topic that will appeal to a wide variety of medical practitioners.